2019
DOI: 10.1016/j.ijmedinf.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

E-tools for hospital management: An overview of smartphone applications for health professionals

Abstract: Background: Commonly, the management of the main hospital activities are organized by different software packages that run on desktop computers which may not always allow a fast and practical use by health operators. This problem could be alleviated through the use of mobile health. The aim of this study was to give an overview of smartphone and tablet applications used for hospital management and administration, in order to evaluate their features and analyse them according to their contents, number of downlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
8
0
2
Order By: Relevance
“…The effect on patient care remains unclear, but usage patterns suggest that electronic access to guidelines is highly appreciated. Mobile phones apps are an emerging tool in health care [24-27], and they are leading to new possibilities, such as applications in patient management, resource distribution, and quality control [28]. Our Web-based system and most of the apps available fall in the category of patient management [28-30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on patient care remains unclear, but usage patterns suggest that electronic access to guidelines is highly appreciated. Mobile phones apps are an emerging tool in health care [24-27], and they are leading to new possibilities, such as applications in patient management, resource distribution, and quality control [28]. Our Web-based system and most of the apps available fall in the category of patient management [28-30].…”
Section: Discussionmentioning
confidence: 99%
“…Mobile phones apps are an emerging tool in health care [24-27], and they are leading to new possibilities, such as applications in patient management, resource distribution, and quality control [28]. Our Web-based system and most of the apps available fall in the category of patient management [28-30]. Some trials investigating the effect of mobile technology have shown that it significantly improves outcomes related to disease management [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mobile applications (apps) represent an opportunity to improve health status and disease management by collecting large data, and play an important role particularly in peer support (patient-to-patient communication), which provides mutual exchange between patients in terms of knowledge, experience, and emotional, social or practical support. In rheumatology, there are nearly 200,000 available apps on Apple or Android devices, however, only a few have been rigorously evaluated and approved with clinical benefits ( 3 ). Patients with rheumatoid arthritis (RA) need regular monitoring by a rheumatologist to achieve good health outcomes, as a result, RA apps have become currently most demanding ones in mobile market ( 4 ), but recent studies assessing the quality of RA apps showed that most of them were not achieving high-quality scores and that data on funding and origin were frequently unavailable ( 5 , 6 ).…”
Section: Main Areas Of Development For Telemedicine In Rheumatologymentioning
confidence: 99%
“…5 6 mHealth might improve care by enabling remote diagnosis and treatment, and reducing healthcare utilisation and costs. [7][8][9][10] mHealth has been studied in cardiac patients to evaluate potential benefits and has shown promising results in several cardiac patient groups. [11][12][13][14][15][16] Last year, a randomised controlled trial on mHealth in patients with heart failure demonstrated a significant reduction of all-cause mortality in patients assigned to the mHealth arm.…”
Section: Introductionmentioning
confidence: 99%